Menjadi Guru Pendidikan Islam yang Sukses Ditengah Liberalisasi Pendidikan: Mencapai Pertumbuhan Siswa secara Maksimal dalam Mengimplementasikan Kurikulum Total - Mustain, Mustain (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2019)
This article aims to describe how to become a successful Islamic education teacher in the midst of educational liberalization: achieving maximum student growth in implementing the total curriculum. This research is a qualitative literature study. Research design becomes a reflexive process at every stage of the research. Qualitative analysis involves two activities: 1) developing an awareness of the types of data that can be examined and how they can be explained; and 2) a number of practical activities that help with data types. From the discussion it can be concluded as follows: 1) Islamic Teaching Higher Education Institutions must re-plan to develop Islamic education teachers, train, and complete deficiencies in their preparation so that they can meet the requirements of the improved curriculum and to develop their educational thinking through a curriculum developed with many additions to educational technology content. 2) The position of the teacher is very strong, the power to influence and motivate as it has been recognized for centuries. Like holding honey and poison. Teachers can shape and influence students' hearts and minds with what is said, done, and how to do it. The teacher's expectations can trigger a desire to learn in a child which can determine their future life opportunities in great things. On the other hand, the teacher can poison the child. Teachers can turn off enthusiasm, reduce hopes and dreams, and turn off their learning paths. 3) Teachers in Islam must be able to integrate Islamic studies with other fields to make them relevant to contemporary needs, the curriculum structure must be improved, academic freedom must be returned to pedagogically mature Muslim academics with the final reference that students have the necessary skills in the workplace and become leaders in the workplace. society, which is more important, except problem-based teaching and improving HoT, teachers in Islam, must integrate themselves as mualim, murabbi, muaddib, murshid and finally preacher, in educating generations of morals explicitly related to pedagogical approaches manifested in various roles. inside and outside the classroom.